1990
DOI: 10.1104/pp.94.1.233
|View full text |Cite
|
Sign up to set email alerts
|

Circumnutations of Sunflower Hypocotyls in Satellite Orbit

Abstract: The principal objective of the research reported here was to determine whether a plant's periodic growth oscillations, called circumnutations, would persist in the absence of a significant gravitational or inertial force. The definitive experiment was made possible by access to the condition of protracted near weightlessness in an earth satellite. The experiment, performed during the first flight of Spacelab on the National Aeronautics and Space Administration shuttle, Columbia, in November and December, 1983… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0
2

Year Published

1992
1992
2011
2011

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 12 publications
(6 reference statements)
4
50
0
2
Order By: Relevance
“…On the other hand, Chapman & Brown (1979) and Brown & Chapman (1988) reported that the circumnutation did not disappear on horizontal and three-dimensional clinostats, although the number of circumnutating seedlings and the amplitude of circumnutation decreased. The latter group obtained qualitatively similar results under microgravity (Brown & Chapman 1984;Brown et al 1990). It has been suggested that the difference between the two groups is due to the difference in the sunflower cultivars used (Zachariassen et al 1987).…”
Section: Why Does Circumnutation Stop On Clinostats?supporting
confidence: 73%
“…On the other hand, Chapman & Brown (1979) and Brown & Chapman (1988) reported that the circumnutation did not disappear on horizontal and three-dimensional clinostats, although the number of circumnutating seedlings and the amplitude of circumnutation decreased. The latter group obtained qualitatively similar results under microgravity (Brown & Chapman 1984;Brown et al 1990). It has been suggested that the difference between the two groups is due to the difference in the sunflower cultivars used (Zachariassen et al 1987).…”
Section: Why Does Circumnutation Stop On Clinostats?supporting
confidence: 73%
“…In this model, earth gravity does not play a crucial and decisive role in generating circumnutations. Studies on sunflower circumnutations in the circumterrestial orbit, which excluded the significance of gravity in generating circumnutations, contributed to the revival of Darwin's model, 12 in which the inner oscillator is an indispensable element in generating circumnutations.…”
Section: Models Of Circumnutation Mechanismmentioning
confidence: 99%
“…19 In Helianthus annuus, changes in the direction may be evoked by a geotropic stimulus; 6 in the microgravity conditions of the circumterrestial orbit, the direction of circumnutations changes more frequently than on the earth. 12 Johnsson 22 shows changes in the direction in the sunflower accompanied by a change in the amplitude and frequency of circumnutations. The study of Israelsson and Johnsson 7 revealed that 60% of the sunflower population studied circumnutated in the ccw direction, and 25%-cw; the others displayed pendulum-like movement.…”
Section: Parameters Of Circumnutations-the Amplitude Period Shape mentioning
confidence: 99%
See 2 more Smart Citations